EFFECTS OF ARBUSCULAR MYCORRHIZA FUNGAL TREATMENT ON INDIGENOUS MICROBIAL COMPOSITION IN THE RHIZOSPHERE OF SELECTED RICE VARIETIES - Okonji, Christopher J; Sakariyawo, Olalekan Suleiman; Okeleye, Kehinde Adebayo; Ajayi, Oluwakayode Emmanuel; Osunbiyi, Adebayo Goodluck (Journal of Agricultural Sciences (Belgrade), 2018)
Plant growth can be stimulated by symbiotic relationship between arbuscular mycorrhiza fungi (AMF) and bacteria within the rhizosphere region. These interactions are highly crucial for soil fertility increased productivity and sustainability, as well as food security considering high level of malnutrition. Six rice varieties grown with (M+) or without (M-) AMF inoculation in a randomized complete block design with three replicates. The soil physic-chemical properties were determined using standard procedures, bacteria were isolated from the soil samples and the colony count was determined during the early and late cropping season of rice. Specific soil properties (phosphate, pH, organic matter) increased dramatically in presence of AMF which led to significant rice yield in both seasons. Bacterial species isolated include Lactobacillus spp., Klebsiella aerogenes, Bacillus subtilis, Escherichia coli, Pseudomonas fluorescens, Azospirillum brasilense, Bacillus subtilis, Staphylococcus aureus, Enterobacter cloaca, and Micrococcus sp. Rice exudates increased bacteria population in early season, whilst AMF treatment increased bacteria population in late season and generally increased the bacteria species richness in the both seasons. Although the actual mechanism that increased the bacteria species richness was not accessed, this study however showed that such increase in specific AMF-bacteria interaction increase and sustains soil fertility which also increases rice yield. Further study is necessary to determine the mechanism of interaction observed between AMF inoculation and bacterial population.